PEMBINAAN BALAI PEMASYARAKATAN KELAS I MAKASSAR TERHADAP ANAK BERKONFLIK DENGAN HUKUM - Rahmat Wardana; Abdul Syatar (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2022)
The phenomenon of children facing the law or in conflict with the law requires special handling that is different from that of adults. Balai Permasyarakatan is one of the parties given the responsibility to be involved in conducting coaching. This study aims to find out how the function of the Balai Permasyarakatan Kelas 1 Makassar in conducting guidance for children who face the law. The research used is descriptive qualitative research with empirical normative and normative theological approaches. The results of this study show that the guidance of children facing the law by the Balai Pemasyarakatan Kelas Makassar is carried out through a personality guidance program, independence and supervision of child clients, especially those who obtain parole. The coaching program carried out by the Correctional Center has provided benefits, by fostering children who face the law before living a normal life in the community.